Profiling Sustainable Environmental Awareness of Primary School Students in Sorong District by Gender and School Location - Ramadany, Lisa Dewi; Sujana, Atep; Sopandi, Wahyu; Hidayat, Febrian Andi (Journal of Science Education Research, 2025)
Sustainable environmental awareness is essential in shaping a generation capable of facing global environmental challenges. The study aimed to map the profile of sustainable environmental awareness of primary school students in Sorong District,considering gender differences and location (urban, suburban, and rural) across three main dimensions: knowledge, attitude, and behavior. Using a survey-based quantitative approach, data we recollected from 132 students through a Likert scale questionnaire. The results showed that male students demonstrated superior conceptual understanding, while female students were more consistent in sustainable behavior. In addition, students in peripheral areas showed the highest awareness across all dimensions.Students in urban areas excelled in collective attitudes, while students in suburban areas had the low awareness. These findings indicate the need for action-based approaches to improve sustainable behavior in male students, community-based engagement for female students,and locally-based programs to increase awareness in the suburban between urban and rural regions.The study highlighted the importance of integrating sustainability education in science subjects, especially in regions with high biodiversity and complex environmental challenges. The findings provide valuable insights for teachers and policymakers in developing sustainability education programs that are contextualized and applicable in regions with similar sociology-environmental characteristics